STUDI KUALITAS FILM PLASTIK BIODEGRADABLE BERBASIS PATI JAGUNG KETAN (ZEA MAYS CERATINA) DENGAN PENAMBAHAN KITOSAN DAN VIRGIN COCONUT OIL (VCO) - Nur Safitri; Rahmaniah Rahmaniah; Iswadi Iswadi (JFT : Jurnal Fisika dan Terapannya, 2021)
Biodegradable plastics are plastics made from renewable sources and are biodegradable and environmentally friendly. To minimize the use of synthetic plastics, research was carried out on the manufacture of biodegradable plastics from glutinous corn starch (Zea mays. Ceratina) with the addition of chitosan and Virgin Coconut Oil (VCO). This study aims to see the quality of the biodegradable plastic film of glutinous corn starch with the addition of chitosan and VCO. The quality test carried out is a mechanical test consisting of a water resistance absorption test, a tensile strength test and an elongation test. FTIR analysis and biodegradability tests were also carried out. The results showed that the water-resistance test results were sample A of 42.86%, sample B of 25% and sample C of 14.29%. To test the tensile strength obtained sample A of 18.1667 MPa, sample B of 0.5171 MPa and sample C of 2.7215 MPa. For the elongation test, sample A was 2.8%, sample B was 3.85%, and sample C was 1.92%. The FTIR analysis results of the three samples showed C-H and O-H groups' presence derived from the constituent materials and the presence of C = O and C-O groups indicating that the hydrogel could be degraded. In the biodegradability test, it is known that the addition of chitosan and VCO during the decomposition of the material because it has anti-microbial properties. The data analysis carried out obtained data that met the SNI value for the tensile strength of sample A.